Form factors of $$\varLambda _b^0 → \varLambda _c(2595)^+$$ Λ b 0 → Λ c ( 2595 ) + within light-cone QCD sum rules - Hui-Hui Duan; Yong-Lu Liu; Qin Chang; Ming-Qiu Huang (European Physical Journal C: Particles and Fields)
Abstract In this work, we calculated the form factors of the weak decay process $$\varLambda _b^0 → \varLambda _c(2595)^+$$ Λ b 0 → Λ c ( 2595 ) + , where the final charm baryon represents an excited state with spin-parity $$\frac{1}{2}^-$$ 1 2 - . Utilizing the light-cone QCD sum rules approach, we incorporated the contributions of the lowest two charm baryon states: the ground state $$\varLambda _c$$ Λ c with $$J^P=\frac{1}{2}^+$$ J P = 1 2 + and the excited state $$\varLambda _c(2595)^+$$ Λ c ( 2595 ) + with $$J^P=\frac{1}{2}^-$$ J P = 1 2 - in the hadronic representation of the $$\varLambda _b → \varLambda _c(2595)^+$$ Λ b → Λ c ( 2595 ) + transition correlation function. This approach allows us to extract the form factors of the $$\varLambda _b^0 → \varLambda _c(2595)^+$$ Λ b 0 → Λ c ( 2595 ) + from $$\varLambda _b^0 → \varLambda _c^+$$ Λ b 0 → Λ c + transition. During the light-cone QCD sum rules procedure, we employed the light-cone distribution amplitudes (LCDAs) of the $$\varLambda _b$$ Λ b baryon. Furthermore, by combining these form factors with the helicity amplitudes of the bottom baryon transition matrix elements, we calculated the differential decay widths for the processes $$\varLambda _b^0 → \varLambda _c(2595)^+\ell ^-\bar{ν }_\ell $$ Λ b 0 → Λ c ( 2595 ) + ℓ - ν ¯ ℓ and provided the optimal choice of the interpolating current for $$\varLambda _c$$ Λ c in this process. Additionally, within the lifetime of $$\varLambda _b^0$$ Λ b 0 , we obtained the absolute branching fractions for the semileptonic decays $$\varLambda _b^0 → \varLambda _c(2595)^+ \ell ^- \bar{ν }_\ell $$ Λ b 0 → Λ c ( 2595 ) + ℓ - ν ¯ ℓ . With the branching fractions of $$\varLambda _b^0 → \varLambda _c(2595)^+ \ell ^- \bar{ν }_\ell $$ Λ b 0 → Λ c ( 2595 ) + ℓ - ν ¯ ℓ calculated in this work, we also determined the parameter $$\mathcal {R}(\varLambda _c(2595)^+)$$ R ( Λ c ( 2595 ) + ) which tests the lepton flavor universality. This parameter is defined as the ratio of branching fractions $$\mathcal {B}r(\varLambda _b^0 → \varLambda _c(2595)^+τ ^-\bar{ν }_τ )$$ B r ( Λ b 0 → Λ c ( 2595 ) + τ - ν ¯ τ ) and $$\mathcal {B}r(\varLambda _b^0 → \varLambda _c(2595)^+μ ^-\bar{ν }_μ )$$ B r ( Λ b 0 → Λ c ( 2595 ) + μ - ν ¯ μ ) . Our results provide a valuable theoretical test for these decay channels and offer insights into the LCDAs of bottom baryons, paving the way for further in-depth investigations.